2019
DOI: 10.1007/s10334-019-00773-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal sinus fat and renal hemodynamics: a cross-sectional analysis

Abstract: Objectives Increased renal sinus fat (RSF) is associated with hypertension and chronic kidney disease, but underlying mechanisms are incompletely understood. We evaluated relations between RSF and gold-standard measures of renal hemodynamics in type 2 diabetes (T2D) patients. Methods Fifty-one T2D patients [age 63 ± 7 years; BMI 31 (28-34) kg/m 2 ; GFR 83 ± 16 mL/min/1.73 m 2 ] underwent MRIscanning to quantify RSF volume, and subcutaneous and visceral adipose tissue compartments (SAT and VAT, respectively). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…In a cross-sectional exercise study RSF was not associated with eGFR or uACR at baseline, but had a significant association with uACR post-exercise, after adjustment for multiple variables including VAT (106). In a study of people with type 2 diabetes, RSF had an association with mGFR that remained significant after adjustment for BMI and VAT, but not after adjustment for age (107).…”
Section: Mechanisms Underpinning Renoprotectionmentioning
confidence: 85%
See 3 more Smart Citations
“…In a cross-sectional exercise study RSF was not associated with eGFR or uACR at baseline, but had a significant association with uACR post-exercise, after adjustment for multiple variables including VAT (106). In a study of people with type 2 diabetes, RSF had an association with mGFR that remained significant after adjustment for BMI and VAT, but not after adjustment for age (107).…”
Section: Mechanisms Underpinning Renoprotectionmentioning
confidence: 85%
“…It is hoped that designating fatty kidney as a distinct clinical entity will help to focus research efforts (125). In longitudinal studies of changes in renal ectopic fat depots after metabolic surgery, it remains a challenge to separate the effect of RSF reduction from concomitantly occurring VAT and total body fat reductions (107). Despite this, future studies of metabolic surgery should include measurements of renal sinus and peri-renal fats pre-and post-intervention to further characterise the contribution of ectopic kidney fat reduction to its renoprotective effects.…”
Section: Mechanisms Underpinning Renoprotectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, obesity has been linked to DKD by provoking glomerular hyperfiltration, secondary to changes in sodium retention and increased sympathetic nervous system activity [42]. Intrarenal fat deposition ('fatty kidney'), in particular fat accumulation in the renal sinus (RSF), has been linked to hypertension [43], renal inflammation and fibrosis, and unfavorable renal hemodynamic function [44]. Intervention trials aimed at weight loss have indeed showed evidence for renoprotection.…”
Section: Obesity and Insulin Resistancementioning
confidence: 99%